Effects of “Football and Nutrition for Health” program on body composition, physical fitness, eating behaviours, nutritional knowledge, and psychological status among 7 to 10 years school children - Morgado, Micaela C.; Sousa, Mónica; Coelho, André B.; Vale, Susana; Costa, Júlio A.; Seabra, André (Frontiers in Pediatrics, 2023)
Introduction: Noncommunicable diseases and obesity are between the major health threat due to consumption of unhealthy foods and limited time spent on physical activities, a situation of particular concern among children. Since children spend most of their time at school, this study intends to investigate the effect of a school intervention program, which combines recreational football and nutrition education, on body composition, physical fitness, physical activity, blood pressure and heart rate, eating behaviours, nutritional knowledge, and psychological status in elementary school children. Methods: A total of 67 children, between 7 and 10 years old, were allocated into three groups: the Football Group (FG) which held 2 weekly sessions of 60 minutes of recreational football, the Nutrition and Football Group (NFG) which held 2 sessions per week of 60 minutes of recreational football plus 60 minutes of nutritional education and the Control Group (CG) which maintained its usual curriculum. The intervention lasted 12 weeks. All measurements were collected before and after the intervention. Results: Intervention groups significantly (p < 0.05) improved BMI Z-score, rest heart rate, horizontal jump and shuttle test, physical activity level, and psychosocial health. The NFG group significantly decreased (p < 0.05) waist-to-height ratio and blood pressure, and significantly increased (p < 0.05) nutritional knowledge, fruit, and fish consumption. While FG significantly decreased (p < 0.05) the percentage of fat mass and significantly increased (p < 0.05) muscle mass and performance in the 20m sprint. This is a provisional file, not the final typeset article Discussion: The results have shown to improve nutritional status, explosive strength, aerobic and neuromuscular fitness, as well as increase the level of physical activity. The nutritional education sessions contributed to increase nutritional knowledge and to improve the consumption of healthy food groups in a ludic-educational way. The "Football and Nutrition for Health" program was able to induce short-term improvements in several health markers, highlighting the role of the school curriculum in children's health.